2018
DOI: 10.3390/w10020149
|View full text |Cite
|
Sign up to set email alerts
|

Land Use Change over the Amazon Forest and Its Impact on the Local Climate

Abstract: One of the most important anthropogenic influences on climate is land use change (LUC).In particular, the Amazon (AMZ) basin is a highly vulnerable area to climate change due to substantial modifications of the hydroclimatology of the region expected as a result of LUC. However, both the magnitude of these changes and the physical process underlying this scenario are still uncertain. This work aims to analyze the simulated Amazon deforestation and its impacts on local mean climate. We used the Common Land Mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
39
0
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 32 publications
5
39
0
11
Order By: Relevance
“…The significant and negative associations between the vertical profile of GPH and cropland fraction could be explained by a denser air column associated with tropospheric cooling (Snyder 2010), as cold air is more dense than warm air, causing pressure surfaces to be lower. This positive relationship between temperature and GPH is also revealed in a number of studies (Nikolic et al 2019, Tomczyk andBednorz 2019), although some negative relationships may be found at the surface level (Liopart et al 2018). The correlation patterns of cropland fraction with temperature and GPH at different levels are generally insensitive to our focus on significantly increasing cropland regions and to our choice to detrend variables (figures S12-S14), as well as to the magnitude of interannual variability of cropland fraction data (figures S15 and S16).…”
Section: Cropland Expansion Cools the Full Troposphere And Alters Trosupporting
confidence: 65%
“…The significant and negative associations between the vertical profile of GPH and cropland fraction could be explained by a denser air column associated with tropospheric cooling (Snyder 2010), as cold air is more dense than warm air, causing pressure surfaces to be lower. This positive relationship between temperature and GPH is also revealed in a number of studies (Nikolic et al 2019, Tomczyk andBednorz 2019), although some negative relationships may be found at the surface level (Liopart et al 2018). The correlation patterns of cropland fraction with temperature and GPH at different levels are generally insensitive to our focus on significantly increasing cropland regions and to our choice to detrend variables (figures S12-S14), as well as to the magnitude of interannual variability of cropland fraction data (figures S15 and S16).…”
Section: Cropland Expansion Cools the Full Troposphere And Alters Trosupporting
confidence: 65%
“…[10][11][12], and RCMs can be run for both past and future climates. They can be applied to sensitivity experiments (e.g., the response of cyclogenesis to South America (SA) topography 13 ), climate process studies (such as the surface-atmosphere interaction 14,15 ), seasonal climate forecast, 16,17 interannual variability, 12,[18][19][20][21] climate extreme events, 22 monsoons, 23 and climate projections, [24][25][26] just to mention a few applications. Therefore, RCMs allow the climate processes to be assessed, the impacts of climate change to be projected, 27 and also help decision makers to come to conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…A compreensão sobre a magnitude destes impactos em escala global se torna essenciais para o estabelecimento de estratégias de adaptação e mitigação das perdas e danos causados por alterações climáticas (Ren et al, 2013;Llopart et al, 2018). No entanto, a avaliação dos impactos na América do Sul e no Brasil ainda é uma tarefa cientificamente desafiadora por haver uma quantidade limitada de informações sobre mudanças climáticas pretéritas e sobre as estimativas de impactos futuros para o Brasil (Geirinhas et al, 2017;Feron et al, 2019).…”
Section: Introductionunclassified
“…As tendências positivas de aumento da ocorrência destes eventos cobrem áreas maiores do que aquelas áreas que apresentam tendências negativas (Collins et al, 2009;Reguero et al, 2019). Em termos de América do Sul (AS), grande parte dos estudos estão concentrados em entender as variações climáticas que ocorrem especificamente sobre determinadas regiões, como a região Amazônica (Llopart et al, 2018), a Bacia do Prata (Bettolli e Penalba, 2018;Montroull et al, 2018), regiões mais ao Sul do continente (Kayano e Setzer, 2018;Detzer et al, 2019), além das regiões Sudeste (Coelho et al, 2016), Nordeste (Oliveira et al, 2017) e Sul (Cordeiro et al, 2016) de 1948-1976 indicando aumento da (ou das duas) temperatura extrema (mínima ou máxima). No entanto, o cálculo de séries climáticas diárias cobrindo 20 ou 30 anos pode não ser suficiente para indicar alterações em padrões atmosféricos e oceânicos.…”
Section: Introductionunclassified